2015
DOI: 10.1093/trstmh/tru187
|View full text |Cite
|
Sign up to set email alerts
|

Entomological impact and social participation in dengue control: a cluster randomized trial in Fortaleza, Brazil

Abstract: BackgroundThis study intended to implement a novel intervention strategy, in Brazil, using an ecohealth approach and analyse its effectiveness and costs in reducing Aedes aegypti vector density as well as its acceptance, feasibility and sustainability. The intervention was conducted from 2012 to 2013 in the municipality of Fortaleza, northeast Brazil.MethodologyA cluster randomized controlled trial was designed by comparing ten intervention clusters with ten control clusters where routine vector control activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
1
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(133 citation statements)
references
References 11 publications
2
115
1
15
Order By: Relevance
“…Faktor status ekonomi dan pola pekerjaan berpengaruh pada paparan maupun keparahan penyakit DBD tersebut. 3,4 Aktivitas pembangunan tidak terencana, daya dukung lingkungan berkurang, penampungan air dan sanitasi dasar tidak layak, serta pola hidup masyarakatnya yang berubah semakin meningkatkan transmisi. 5,6 Selain itu, terdapat faktor-faktor risiko lain yang disebabkan oleh perubahan demografis suatu wilayah, yaitu pemukiman di daerah perkotaan yang semakin padat, juga sistem transportasi yang semakin baik yang menyebabkan mobilitas penduduk semakin tinggi, serta tingkat urbanisasi yang sulit dikontrol.…”
Section: Pendahuluanunclassified
“…Faktor status ekonomi dan pola pekerjaan berpengaruh pada paparan maupun keparahan penyakit DBD tersebut. 3,4 Aktivitas pembangunan tidak terencana, daya dukung lingkungan berkurang, penampungan air dan sanitasi dasar tidak layak, serta pola hidup masyarakatnya yang berubah semakin meningkatkan transmisi. 5,6 Selain itu, terdapat faktor-faktor risiko lain yang disebabkan oleh perubahan demografis suatu wilayah, yaitu pemukiman di daerah perkotaan yang semakin padat, juga sistem transportasi yang semakin baik yang menyebabkan mobilitas penduduk semakin tinggi, serta tingkat urbanisasi yang sulit dikontrol.…”
Section: Pendahuluanunclassified
“…Research has repeatedly suggested that vector control requires interventions with intersectorial partnerships, the involvement of local communities, and IVM (28). Embedding social participation in decision-making and environmental management to improve vector control was feasible and significantly reduced vector densities (29).…”
Section: Vector Controlmentioning
confidence: 99%
“…A aceitação de que determinantes biológicos, socioeconômicos e ambientais estão associados à dispersão da maioria das arboviroses exige estratégias de caráter intersetorial que transcendem as ações exclusivas de controle químico do vetor (7)(8)(9) . Estas, que são baseadas em grande medida no uso rotineiro de larvicidas para redução das formas imaturas e na borrifação aérea de adulticidas em períodos de alta transmissão, tem-se mostrado ineficientes na contenção da transmissão e, particularmente, pouco sustentáveis nos mais diversos contextos (5) .…”
Section: Incorporação De Novas Tecnologias Ao Controle Vetorialunclassified
“…No grupo A estão tecnologias que foram testadas com sucesso em alguns cenários, no que se refere principalmente à diminuição da infestação vetorial. Algumas prescindem, em princípio, de controle químico adicional ou alternativo como a Abordagem eco-bio-social, que aposta na forte participação social, educação em saúde, manejo ambiental e articulação intersetorial para eliminação mecânica sistemática de potenciais criadouros (7,10) ; e o uso de compostos naturais com atividades larvicidas, como os óleos vegetais produzidos a partir das cascas de frutas cítricas (10) . Já na experiência com estações dispersoras de larvicidas, realizada em duas cidades do Amazonas, as próprias fêmeas do mosquito carreiam o larvicida para criadouros de difícil acesso, tratando-os quimicamente no momento da ovoposição (10,12) .…”
Section: Dengue Zika E Chikungunya -Desafios Do Controle Vetorial Frunclassified
See 1 more Smart Citation